L’impact de l’inclusion financière sur la stabilité du secteur bancaire algérien- étude économétrique - Rahma MERNIZ; Khaled BENDJELLOUL (Journal of North African Economies, 2025)
The objective of this study is to examine how financial inclusion affects the stability of the banking system in Algeria. This study employs ARDL modeling using distinct indicators belonging to the two quantitative dimensions of financial inclusion as exogenous variables. Our endogenous variable, banking stability, is quantified by an aggregated index that considers various macroeconomic indicators and other microeconomic indicators related to various aspects including profitability, asset quality, solvency, liquidity, and the development of the banking sector. The study findings suggest that despite the positive impact of active bank account access and ownership indicators, this impact is contingent upon the quality of financial system supervision, which ensures a certain level of loan quality.